2011
DOI: 10.1039/c1mt00030f
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional response of Streptococcus pneumoniae to Zn2+ limitation and the repressor/activator function of AdcR

Abstract: Zinc (Zn(2+)) is an important trace metal ion that has been shown to regulate the expression of several (virulence) genes in streptococci. Previously, we analyzed the genome-wide response of S. pneumoniae to Zn(2+)-stress. In this work, we have performed a transcriptomic analysis to identify genes that are differentially expressed under intracellular Zn(2+) limitation. This revealed a number of genes that are highly upregulated in the absence of extracellular Zn(2+), amongst which the genes belonging to the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
90
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(97 citation statements)
references
References 58 publications
(120 reference statements)
6
90
1
Order By: Relevance
“…In addition to genes encoding the Adc/Lmb system, we found a perfect AdcR box in the promoter region (400 bp upstream from the start codon) of 7 supplementary genes or operons (Table 3), in particular, upstream of the adh gene (sak_0087), encoding a potential zinc-containing alcohol dehydrogenase, which has already been identified to be a direct binding target of AdcR in S. pneumoniae (26,42).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…In addition to genes encoding the Adc/Lmb system, we found a perfect AdcR box in the promoter region (400 bp upstream from the start codon) of 7 supplementary genes or operons (Table 3), in particular, upstream of the adh gene (sak_0087), encoding a potential zinc-containing alcohol dehydrogenase, which has already been identified to be a direct binding target of AdcR in S. pneumoniae (26,42).…”
Section: Resultsmentioning
confidence: 85%
“…We have shown that the expression of the lmb, adcA, and adcAII genes is zinc dependent. Zn 2ϩ -dependent regulation is mediated in S. pneumoniae and S. pyogenes by the AdcR regulator (26,27,42). S. pneumoniae AdcR has a unique effector in zinc, and its crystal structure revealed the presence of two metal-binding sites (43).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S. pneumoniae encodes a homologous Zn 2ϩ uptake system (AdcABC) that is regulated by a ZitR homolog (AdcR) (76). AdcR also regulates the expression of the four pneumococcal histidine triad (Pht) proteins, PhtA, PhtB, PhtD, and PhtE (77), involved in surface adhesion, as well as the Zn 2ϩ -specific AdcA homolog AdcAII and a Zn 2ϩ -dependent alcohol dehydrogenase (78,79). The adc operon is present in most streptococci and has also been studied in Streptococcus gordonii, where it is involved in Mn 2ϩ homeostasis (80), and in Streptococcus suis, where it regulates the expression of a Zn 2ϩ /Mn 2ϩ uptake system, ribosomal genes, and pht genes (81).…”
Section: One-component Systemsmentioning
confidence: 99%
“…It may act as a structural element, helping to maintain the conformation of particular protein domains, or as a catalytic cofactor in the active site of a variety of enzymes (13). Zinc sensing in bacteria is carried out by regulators of different families, including SmtB/ ArsR, MerR, TetR, MarR, and the Fur family (10,26,32,37,54). Zur (zinc uptake regulator) proteins belong to the Fur family.…”
mentioning
confidence: 99%